Experimental study of the potential for extending the process limits in multi-stage forming of micro gears from sheet metal by a local short-term laser heat treatment - Leicht, Miriam; Kraus, Martin; Rohrmoser, Andreas; Merklein, Marion (Materials Research Proceedings 2023, 2023)
Cold forming of micro gears is currently not possible for modules m < 0.2 mm due to the occurrence of high tool stresses, handling problems and size effects. A multi-stage process chain of micro bulk forming from sheet metal offers the potential to solve these challenges. However, the industrial applicability is limited due to material efficiency. Against this background, the aim of this research work is an improvement of the material utilization as well as a further reduction of the tool stresses. Therefore, the influence of different heat treatment strategies as well as the materials copper Cu-OFE and brass CuZn30 are analyzed. Thus, a local laser heat treatment and a global heat treatment of the blanks are investigated. The focus of this research work is on the first process stage, pin extrusion, which is used for forming of the wheel blank. Since this process setup provides the material for the further forming stages, it has a huge influence on the material efficiency and on the forming of the gearing in the second process stage. Therefore, the component and process properties are evaluated to assess the influence of the measures. The results prove higher material efficiency at a similar tool stress by using local short-term heat treatmen